Identification of Amplified Fragment Length Polymorphism Fragments Linked to Fruit Skin Colour of Oil Palm (Elaeis Guineensis Jacq.) - Seng, Tzer Ying (2005)
Oil palm (Elaeis guineensis Jacq.) is an important commercial oil crop. It can be classified by its fruit colour into two types: a) nigrescens (Nig) type which is dark violet (unripe) and turning to reddish violet (ripe), and b) virescens (Vir) type which changes from green colour (unripe) to orange (ripe). Vir and Nig are monofactorially inherited, with Vir dominant over Nig. The different degrees of ripeness during harvesting of the fruits would influence the quantity and quality of oil in the mesocarp. The oil palm harvesting system is based on a minimum ripeness standard whereby the workers use the number of fruits detached from a bunch as a measure of its ripeness. Most of the oil palms grown commercially are the Nig type, being the more common type in the wild. However, Vir is an economically important trait as it is much easier to determine the degree of ripeness in Vir fruits. Molecular markers are powerful tools with the potential to influence plant breeding. Segregating populations for fruit colour CBP line which is dura x tenera cross and NPC1 line, tenera x tenera cross were obtained from Pamol Plantation. Obtaining high quality DNA from mature leaves was difficult. Therefore, a protocol of DNA isolation was developed in this study after 12 different extraction methods were attempted. The aim of this project was to identify Amplified Fragment Length Polymorphism (AFLP) primer combinations and markers that have the potential to distinguish the fruit skin colour trait of oil palm by using the AFLP-based Bulked Segregant Analysis (BSA) technique. Of the 64 primer combinations, 10 primer combinations for CBP line and four primer combinations for NPC1 line were selected. In study 1, only three bands that showed 100% specificity to fruit colour differentiation which are regarded as fruit skin colour-specific markers were obtained for both lines, respectively. In study 2, there were four and eight specific bands which showed 80% probability of significant association to the fruit skin colour trait in CBP and NPC1, respectively. Primer B12 (E-ACT/M-CAT) generated fragments 142.13 bp and 355.76 bp as Vir-specific markers for CBP line and NPC1 line, respectively. It gave 83.30% (CBP) and 83.70% (NPC1) accuracy to distinguish Vir in study 2. Primer combination B13 (E-ACT/M-CTA) targeted 253.79 bp as the Nig–specific marker for both lines. It gave 76.50% (CBP) and 75.70% (NPC1) of confidence in differentiating the trait in study 2. The sequences of the AFLP markers were considered to be too short for reliability as specific markers. For an efficient MAS, it is therefore highly desirable to convert the linked markers into sequence-specific primers, such as STS, SCAR, STMS or CAP. Dice similarity coefficient (Nei and Li 1979) chosen to estimate the genetic similarity of the progenies studied, which gave average similarities of the CBP progenies of 0.790±0.057 and the NPC1 progenies of 0.761±0.089. The values derived from this study were almost similar showing that the progenies are variable only at their segregating trait. The dendrograms generated by cluster analysis using NJ based on similarity coefficients indicated the applicability and reliability of AFLP polymorphism for distinguishing the two varieties in both lines.